The DEBT POLICY AND OWNERSHIP STRUCTURE OF FIRM IN INDONESIA STOCK EXCHANGE - Taolin, Maximus Leonardo (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2020)
This study examines the effect of ownership structures (insiders ownership, shareholders dispersion and institutional investors) on debt policy. The variable that has a significant influence is institutional investors, while the insiders ownership variable has no significant effect but the direction of the inverse relationship with the debt ratio is in accordance with the theory. Shareholders dispersion variable does not have a significant influence and the direction of the relationship is not in accordance with the theory. These results indicate that the presence of institutional investors can reduce the role of debt in monitoring the behavior of managers, thereby reducing the total agency costs. Control variable. shows growth opportunities, firm size, asset structure and profitability affect the debt ratio and can be used as an instrument to support debt policy to minimize agency costs. Whereas dividend payments and tax rates are not. Using a sample of all companies listed on the Indonesia Stock Exchange other than insurance and financial companies with a research period between 2008 and 2011